PENGAWASAN DEWAN PERWAKILAN RAKYAT DAERAH TERHADAP PENDAPATAN ASLI DAERAH PADA SEKTOR PERHUBUNGAN LAUT DAN DARAT DI KABUPATEN BUTON TENGAH - La Ode Abdul Hamid; Sitti Aisyah; Safiani Safiani (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2023)
The purpose of this study was to determine the implementation of the DPRD’s supervisory function on PAD in Central Buton Regency and the obstacles in the DPRD’ supervisory function of PADin central Buton Regency. This research is a type of normative juridical research with a law approach which takes place in ino month in Central Buton Regency. The result of this study indicate that: (1) DPRD’s supervisory function of PAD can be divided into two, namely, supervision carried out oytside the DPRD building and supervision carried out outside the DPRD building and supervision carried out inside the DPRD building ; (2) The obstacles are DPRD members who lack adequate intellectual abilities, adequate levels of education, education levwls which have implication for the less than optimal role of DPRD, both institutional and individual roles, and lack of human resources in the sea and land transportation sector. The research suggests: DPRD members in carrying out their supervision must have intellectual abilties, further improve education and must increase adequate human resources